Reporting an Unsettled Countryside: The News Media and Rural Protests in Britain - Michael Woods (Culture Unbound: Journal of Current Cultural Research, 2010)
Most analyses of the role of the media in shaping and reproducing popular discourses of rurality have focused on film, television drama and literature. Comparatively little attention has been directed towards the role of the news media in framing perceptions of contemporary rural issues through reportage and commentary. This paper examines the engagement of the news media with a series of rural protests that developed in Britain between 1997 and 2007 around issues such as hunting and farm incomes. The news media had been complicit in maintaining the previous discursive construct of the countryside as a settled and almost apolitical space, but the emergence of major rural protests forced a shift in the representation of rural life. News coverage of rural issues and rural protests increased with the adoption of a new discourse of the “unsettled countryside”. In adjusting to shifting news values, the news media initially bought and reproduced the frames promoted by the major rural campaign group, the Countryside Alliance, including tropes of the “countryside in crisis”, the “countryside comes to town” and the “countryside speaks out for liberty”. Over time, however, a more complex web of representations developed as the perspectives adopted by different media outlets diverged, informed by political ideology. As such, it is argued that the news media played a key role not in only in mediating public reception of rural protests, and thus modulating their political significance, but also in framing the rural protests for participants within the rural community, and as such contributing to the mobilisation of a politicised rural identity and an active rural citizenship.